Tourism Resilience Through the Integration of Adaptation, Mitigation, and Transformation Towards Sustainable Tourism - Lastiani Warih Wulandari (Eduvest - Journal of Universal Studies, 2026)
Tourism resilience is a key concept in maintaining the sustainability of destinations in the face of various crises such as pandemics, natural disasters, climate change, and socio-economic pressures. Global tourism faces increasingly complex dynamics of uncertainty, especially due to climate change, health crises, and socio-economic fluctuations. This condition requires tourism destinations to strengthen their resilience capacity through integrated adaptation, mitigation, and transformation strategies. This study aims to analyze the resilience process of destinations through three main pillars, namely adaptation, mitigation, and transformation that contribute to sustainable tourism development. Using a descriptive qualitative research method, data was collected through literature review. The results show that tourism resilience is formed through operational adaptation strategies, community-based risk mitigation, and transformation of tourism models towards long-term sustainability. Adaptation is carried out through diversification of tourism products, digitization of services, and strengthening community capacity. Mitigation is directed at reducing emissions, resource efficiency, and implementing green tourism standards. Meanwhile, transformation has emerged as a strategic phase that rearranges governance, business models, and destination development orientations to be more inclusive and resilient. These findings strengthen the understanding that resilience is not only the ability to recover from a crisis, but also the ability to grow and transform into a more resilient and innovative tourism system by identifying destination response patterns in managing risks and creating long-term stability so that it can realize sustainable tourism that is able to respond to crises while creating new value.